Evaluasi Pelaksanaan Keadilan Restoratif Dalam Kebijakan Penegakan Hukum Di Indonesia - Arya Nugra Dewangga; Muhammad Rafli Putra Sugiana; Asmak Ul Hosnah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
In implementing the concept of restorative justice, law enforcement in Indonesia still faces many challenges, particularly in terms of consistency, understanding among law enforcement officers, and coordination between institutions. Restorative justice is a methodology aimed at achieving a more socially just and humanistic form of justice by focusing on restoring relationships between the offender, the victim, and the community. In this study, a normative juridical approach is used to assess the implementation of restorative justice in Indonesia’s law enforcement policies. Legislation, government regulations, and their application by law enforcement officers are evaluated for analysis. The results of the study show that although the principles of restorative justice have been incorporated into several laws, their implementation remains suboptimal. Limited human resources, lack of officer training, and the absence of a uniform understanding of the objectives of restorative justice among law enforcement officials are some of the main factors hindering its implementation.